Fatores que influenciam na opção do modo de transporte de crianças para a escola - estudo de caso São Carlos/SP - Rosa, Fernanda Duarte (Universidade Federal de São Carlos, 2011)
In the late years, the number of children who go to school by active modes of transport has decreased significantly. This fact causes several problems both in the area of urban transport (creating traffic congestions and accidents in the school neighborhood during the periods of starting and finishing classes) and in the area of public health (increasing the indices of child obesity). In this context, the objective of this research is to identify which factors influence the mode choice of elementary school children to access the schools. The focus of the research are the public elementary schools, because the geographic area that these schools traditionally serve (neighborhoods) permits that the trips be made by non motorized modes, for a great fraction of the students. The case study was developed in the city of São Carlos, SP with students that attend Municipal Elementary Schools. The survey was carried with the students´ parents by means of questionnaires about the children s personal characteristics, as well as their perception of the route from the residence to the school. The data showed that several factors influence the mode choice for the children trip to school, like the perception of safety and security in the neighborhood, the automobile availability in the residence, the parents habits and culture in relation to the motorized modes of transport and the distance for the residence to the school (the factor that proved to have the strongest impact in the parents decision). The discrete choice models were chosen for the estimation of the modal choice because they are largely used in transportation studies. Among the models that were tested, the multinomial logit was the most adequate. The calibrated model showed satisfactory and significant results, demonstrating that the chosen approach is adequate to the analysis of the mode choice for the trips of children to school.
Keywords: Engenharia urbana; Transportes - planejamento; Escolas; Transporte não motorizado; Modelo de opção modal; School transportation; Non-motorized transport; Mode choice models; ENGENHARIAS